2015
DOI: 10.1021/jp510205u
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive in Situ Characterization of Molecular Structures at the Surface and Buried Interface of Silicon-Supported Low-k Dielectric Films

Abstract: As low-k dielectric/copper interconnects continue to scale down in size, the interfaces of low-k dielectric materials will increasingly determine the structure and properties of the materials. We report an in situ nondestructive characterization method to characterize the molecular structure at the surface and buried interface of silicon-supported low-k dielectric thin films using interface sensitive infrared-visible sum frequency generation vibrational spectroscopy (SFG). Film thickness-dependent reflected SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 82 publications
(136 reference statements)
0
42
0
Order By: Relevance
“…The loss of terminal Si–CH 3 groups is attributed to removal of terminal organic groups by both the plasma etching applied to transfer the photolithographically defined pattern and the plasma ashing and wet cleans applied to remove the hardmask and polymeric plasma-etching residues [32,4648]. The correlation between the decrease in the SiC–H 3 absorbance and fin width is attributed to the limited penetration depth and diffusion length for ions, radicals and other chemically active species present during plasma etching and ashing, and wet cleans through the overlying hard mask and the interconnected porosity in the organosilicate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of terminal Si–CH 3 groups is attributed to removal of terminal organic groups by both the plasma etching applied to transfer the photolithographically defined pattern and the plasma ashing and wet cleans applied to remove the hardmask and polymeric plasma-etching residues [32,4648]. The correlation between the decrease in the SiC–H 3 absorbance and fin width is attributed to the limited penetration depth and diffusion length for ions, radicals and other chemically active species present during plasma etching and ashing, and wet cleans through the overlying hard mask and the interconnected porosity in the organosilicate.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of elastic modulus, the 500 nm and 90 nm fins, when considered as homogeneous structures exhibit increases of 14% and 40%, respectively, with respect to the 3.5 GPa modulus of the unpatterned blanket film [34]. Both the increase in elastic modulus and decrease in SiC–H 3 absorbance with the decrease in fin width suggest a conversion of the hybrid nanoporous organosilicate fins to a stiffer SiO x matrix [48]. In fact, additional depth-dependent CR-AFM measurements [42] and detailed modeling to include possible structural inhomogeneities and edge compliances have shown that about 20 nm of the top and sidewalls of the 90 nm fins consist of a thin “crust” layer with increased stiffness ( E = 7.9 ± 2.2 GPa) relative to the remaining bottom portion of the fin that has mechanical properties closer to those of the unpatterned organosilicate ( E = 3.4 ± 0.8 GPa).…”
Section: Resultsmentioning
confidence: 99%
“…110 In another work, a method using the interference between the surface and the interface SFG signals was used to derive the buried interfacial signal of PMSQ at silicon interface. 111 Plasma etching was commonly used during the incorporation of low- k materials to the electronic interconnections. However, uncontrolled plasma treatment may harm the porous low- k films.…”
Section: Understanding Adhesion Mechanism At Polymer Interfacesmentioning
confidence: 99%
“…One example is the interfaces between polymer and adhesives, which have been reviewed previously. [102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120] Another example is the rubbing and sliding between two polymers, which will be discussed in the following section.…”
Section: Interface Between Polymer and Polymermentioning
confidence: 99%
“…water) interface, polymer/ polymer interface, polymer/metal interface, and polymer/semiconductor interface in the past 10 years. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] By combining SFG and FTIR, we were able to directly detect the molecular structures, especially water structures, at the surface and buried interface of a PMSQ film and thus correlate the molecular structures to the lowk property and reliability. It was found that water molecules tend to form strong hydrogen bond with PMSQ at the PMSQ/air surface (chemisorbed water) and PMSQ/SiO 2 buried interface while more weakly hydrogen bonded water was observed in the bulk (physisorbed water), 20 which provided direct evidence that water at the surface/buried interface plays more important roles in the low-k reliability and property degradation than that in the bulk because chemisorbed water cannot be completely removed by normal annealing process compared to physisorbed water.…”
Section: Introductionmentioning
confidence: 99%